2015
DOI: 10.3233/xst-150496
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characterization and image quality evaluation of the AIRO mobile CT scanner

Abstract: Radiation dose and image quality from a recently introduced mobile CT imaging system are presented. Radiation dose was measured using a conventional 100 mm pencil ionization chamber and CT polymethylmetacrylate (PMMA) body and head phantoms. Image quality was evaluated with a CATPHAN 500 phantom. Spatial resolution, low contrast resolution, Modulation Transfer Function (MTF), and Normalized Noise Power Spectrum (NNPS) were analyzed. Radiation dose and image quality were compared to those from a multi-detector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…The effect of reconstruction filter is shown in [Fig. (b)], with the sharp reconstruction filter giving highest MTF, falling to 10% at ~0.55 mm −1 and limiting resolution down to ~(1/2/0.55) = 0.9 mm feature size, consistent with previously published work …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The effect of reconstruction filter is shown in [Fig. (b)], with the sharp reconstruction filter giving highest MTF, falling to 10% at ~0.55 mm −1 and limiting resolution down to ~(1/2/0.55) = 0.9 mm feature size, consistent with previously published work …”
Section: Resultssupporting
confidence: 89%
“…Previous studies reported the performance of the mobile CT scanner within the context of its primary indication in image‐guided spine surgery. Weir et al assessed the Airo in terms of its imaging performance in comparison to MDCT for image‐guided surgery, including dosimetric characterization and image quality analysis. Their work showed spatial resolution up to 4 lp/cm in the head field‐of‐view (FOV) for the mobile scanner, compared to 7 lp/cm resolution from a Siemens Sensation 64‐slice MDCT scanner for the same FOV .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding image quality, the compromises made to enable the device to be handy and mobile, and to allow the large gantry opening were at the expense of a reduced image quality . This is reflected in the values of subjective image quality where the best rating was not assigned (see Figure with a typical example).…”
Section: Discussionmentioning
confidence: 99%
“…The radiation exposure to the patient is difficult to assess, as CT radiation doses are hardly comparable to fluoroscopy doses. Compared with radiation doses of stationary CT scanners, the doses with the Airo seem to be comparable or slightly higher . Usually, after osteosynthesis of the acetabulum, a postoperative CT is the standard imaging to verify the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%